Analisis Keamanan Informasi pada Sistem Informasi Akuntansi di Era Digital - Jelita Yulianti Br Sitanggang; Lestari Br Tohang; Yuliana Simatupang; Muhammad Rizal (JOURNAL SAINS STUDENT RESEARCH, 2025)
The development of digital technology has had a major impact on accounting information systems (AIS), especially in terms of information security. In the digital age, cybercrime threats such as phishing and data manipulation are on the rise as the internet is increasingly used for financial transactions (Kumala Sari, 2023). To address these risks, various modern accounting technologies have been implemented. Blockchain technology is considered capable of improving the reliability of financial reports by providing transaction records that are immutable and verified in real time (Fajriyah, n.d.). In addition, the use of cloud computing allows flexible data access and supports rapid decision-making, although it still presents challenges in the form of data leaks and cyber attacks (Lubis & Firdaus, 2024). The implementation of Enterprise Resource Planning (ERP) has also been proven to improve integration, efficiency, and financial transparency within organizations (Andine Sekar Kinanti et al., 2024; Mujahidah et al., 2025).This study uses a qualitative method through a literature review of ten scientific articles published in 2023–2025 that are relevant to the theme of information security in SIA. The results of the study show that the successful implementation of SIA in the digital era depends not only on technological sophistication but also on the readiness of human resources, regulations, and adequate governance policies (Fertyno Situmeang et al., n.d.; Novida, 2025). Thus, strengthening information security in SIA requires a combination of technological strategies, increased digital literacy, and comprehensive regulatory protection.